The Cost of Treating Neonates in Intensive Care Unit in a Tertiary Level Teaching Hospital - Basnet, Sahisnuta; Adhikari, Suraj; Timilsina, Mukunda (Nepal Medical College Journal, 2021)
Neonatal intensive care is associated with high costs world-wide and remains a matter of financial stress for families. This is an issue of great importance in a developing country like ours as financial burden may have a negative impact in the overall outcome of a newborn. The objective of this study was to evaluate the direct cost of treating newborns by family members in a neonatal intensive care unit (NICU). This was a prospective cross sectional study carried out in the NICU of Manipal Teaching Hospital, Pokhara, Nepal. There were 96 neonates included in this study over a period of 3 months from September to November 2020. The average cost per neonate per day was NRs. 5858 (USD 50). The highest health expenditure was incurred in neonates of gestational age of 32 to less than 37 weeks, and it was also significantly higher in neonates having birth weights less than 1.5kg. Preterms with hyaline membrane disease, followed by newborns with meconium aspiration syndrome resulted in maximum health costs. Maximum expenditure of the total bill was due to the cost of the bed charges. The median length of stay in the study was 5 days and the length of stay was directly and significantly related to the treatment costs.